Ecotoxicity studies of antifungal metabolites of Bacillus sp. IBA 33 - Gordillo, M. A. (2015)
Abstract: The increments of plant diseases caused by theproliferation of fungicide-resistant pathogens intensified theresearch of new active metabolites against them. The study ofbiological methods as an alternative to chemical control has reachrelevance in recent years. It has been suggested that the use ofmetabolites from Bacillus, is an alternative or supplementarymethod to chemical plant protection, if they are not toxic for theconsumers and environmentally friendly. The toxicity of differentconcentrations of antifungal metabolites produced by Bacillus sp.IBA 33 was evaluated. Their ability to induce cytotoxic effects wasinvestigated by different tests as hemolysis, and Artemia salina andAllium cepa L immobilization. With 2.56 mg/ml of antifungalmetabolites hemolysis reached 24.07%, to 1.28 mg/ml was 14%.HC50 was 10.41 mg/ml. A. salina nauplii exposed to 3.2, 1.6 and 0.8mg/ml of antifungal metabolites showed 80, 20 and 10% of mortalityrespectively; LD50 was 2.24 mg/ml. In Allium cepa L test after 72 hof treatment, the roots lengths were 8.75, 10.35 and 23.75 mm with3.2, 1.6 and 0.8 mg/ml of antifungal metabolites respectively. TheEC50 was 0.078 mg/ml. After 144 h the EC50 was 4.11 mg/ml. Onlywith 3.2 mg/ml of metabolites, chromosomal aberrations, cytoplasmvacuolization and decentralization of nuclei were observed in thecells of Allium cepa L. No micronuclei were detected. Under theexperimental conditions, the antifungal metabolites concentrationsassayed are considered non toxic.